Effect of water stress on growth, productivity and water expense efficiency of summer rice - SARKAR, S (The Indian Journal of Agricultural Sciences, 2014)
A field study was carried out during 1997 and 1998 cropping seasons on a tine loamy (Typic Ustochrept) soil type, to assess the performance ofÂ IET 4786’ summer rice (Oryza sativa L.) under stressed (intermittent ponding) and non-stressed (continuous ponding) situations. In case of intermittent ponding, irrigation was given when soilmoisture tension at 20 cm depth attained the suction value of 0-02 M Pa. Entire irrigation period was divided into 3 stages, ie early [11 to 30 days after transplanting (DAT), middle (31 to 60 DAT) and late (61 to 80 DAT) stages. Intermittent ponding was imposed at single, ie in early (I2) middle (I3) and late (I4) stage or at two stges, ie early plus middle (I5) early and late (I6) and middle plus late (I7) stages. Besides, there were 2 more irrigation regimes, ie continuous ponding was maintained throughout the entire irrigation period (I11) and intermittent ponding was maintained during the entire irrigation period (Ig). The highest grain yield (6.79 Mg ha) was attained under I1, followed by yield of 6.71 Mg ha under 12, Grain yeild mllrkedly decreased under 13, I5, 17 regimes and it attained lowest value (5.37 Mg ha) under Is. Water expense efficiency (Wee) value attained the lowest level (5.26 kg/halmm) under 17 regime. While it was highest (5.99 kg/halmm) under I8 regime and this Wee value was 8.7% higher over I1. Though grain yield attained lowest value under 18 but minimum level of water expense value (910.4 mm) responsible towards greater Wee value (5.71 kg/ha/mm) under this treatment.